Performance of Circular Footing on Expansive Soil Bed Reinforced with Geocells of Chevron Pattern - Sanjeev Kumar; Anil Kumar Sahu; Sanjeev Naval (Civil Engineering Journal, 2019)
Results from laboratory model tests performed on circular footing are presented in this paper to understand the performance of geocell reinforced expansive soil. Naturally occurring expansive soil was used in this study as subsoil. Geocells of chevron pattern fabricated from geotextile made up of polypropylene were used to reinforce the soil bed. The parameters studied in this testing program were the placement depth of the geocell mattress, pocket size of geocell and the height of geocell mattress. Contrary to other researchers; the improvement in the performance of reinforced bed is evaluated at a settlement level equal to the failure settlement of unreinforced soil bed. The performance of reinforced bed is evaluated through two non-dimensional factors viz. bearing capacity improvement factor (If) and settlement reduction factor (PRS%). Test results indicated that with the introduction of geocell as reinforcement, a substantial improvement in bearing capacity and decrease in footing settlement can be achieved. Bearing capacity of reinforced bed increases by more than 200% and 81% reduction in footing settlement was achieved by using geocell mattress of optimal dimensions and placing it just below the footing base.